Uso de rizobactérias e espécies forrageiras no controle do nematoide das galhas em arroz irrigado - (:unkn) unknown (Universidade Federal do Pampa, 2021)
More than a hundred nematode species have been reported in upland and flooded rice in many countries, whose yield reductions can reach 70% in soils infested with root-knot nematode. In this context, biological control has gained prominence in research and in the development of new products that are efficient in the management of phytonematodes. In addition, the rotation and succession of crops with non-host winter species help control nematodes, by reducing the pathogen population and contributing to a favorable environment for antagonist species. Thus, the objective of this work was to evaluate the efficiency of rhizobacterial isolates and forage species in the control of root-knot nematode in irrigated rice. The experiments were carried out at the Soil Microbiology and Phytopathology Laboratory and in a greenhouse at the Federal University of Pampa - UNIPAMPA/Campus Itaqui. For the experiment with the use of rhizobacteria, a completely randomized design (DIC) was used, containing 11 treatments and eight replications. The treatments contained ten rhizobacteria and the control. Rice seeds of the cultivar IRGA 424 were used in 500 mll cups with substrate. Inoculation of nematodes in rice plants occurred 30 days after sowing, using a suspension of 2000 eggs of Meloidogyne sp2 and sp3. per installment. The experiment evaluations took place 30 days after inoculation, where root fresh weight, number of galls and eggs per gram of root were evaluated. The experiment with forages was carried out in DIC, with five treatments and six replications. The treatments used were persian clover (Trifolium resupinatum L), vesiculous clover (Trifolium vesiculosum Savi), white clover (Trifolium repens L.) and gherkin (Lotus corniculatus L.) and the control rice cultivar IRGA 424. Forage seedlings were transplanted. from the experimental area of the campus to the 500 ml beakers containing substrate. After 20 days, 5000 eggs of Meloidogyne sp2 and sp3 were inoculated. per installment. The experiment evaluations took place 30 days after inoculation, where root fresh weight, number of galls and eggs per gram of root were evaluated. Data were subjected to analysis of variance by the F test and the means were grouped by the Scott & Knott test (p≤0.05), using the SISVAR statistical program. In the experiment with rhizobacterial isolates, there was a reduction in the number of galls per gram of root for seven of the ten rhizobacterial isolates tested, with an average of 29% reduction. For the number of eggs per gram of root, nine out of ten isolates had a reduction, with an average of 26%. In the forage experiment, all treatments reduced the number of galls (mean 89.8%) and eggs (mean 92.3%) per gram of root. All forage plants had a reproduction factor less than 1, differing from the control. According to the results, it is concluded that for the experiment with rhizobacteria, the isolates with the greatest reduction of galls and eggs per gram of root were M9, U13, I14, U4 and I16, and, in the experiment with forages, all the species tested were resistant to the rootknot nematode.
Use of rhizobacteria and forage species in the control of the root-knot nematode in irrigated rice
Keywords: Oryza sativa L.; Rotação de culturas; Isolados rizobacterianos; Meloidogyne sp.; Crop rotation; Rhizobacterial isolates; CNPQ::CIENCIAS AGRARIAS